Microstructural, physical, and fluid dynamic assessment of spinel-based and phosphate-bonded investments for dental applications - Innocentini, Murilo D. M.; Chacon, Welton S.; Caldato, Rafael F.; Paula, Gustavo R.; Adabo, Gelson Luis [UNESP] (Wiley, 2015)
This work reports the experimental evaluation of physical and gas permeation parameters of four spinel-based investments developed with or without inclusion of sacrificial fillers. Data were compared with those of three commercial formulations. Airflow tests were conducted from 27 to 546°C, and permeability coefficients were fitted from Forchheimer's equation. Skeletal densities found for spinel- (ρs = 3635 ± 165 kg/m3) and phosphate-bonded (ρs = 2686 ± 11 kg/m3) samples were in agreement with the literature. The developed investments were more porous and less permeable than commercial brands, and the differences were ascribed to the different pore morphologies and hydraulic pore sizes of ceramic matrices. The inclusion of both fibers and microbeads resulted in increases of total porosity (42.6–56.6%) and of Darcian permeability coefficient k1 (0.76 × 10−14–7.03 × 10−14 m2). Air permeation was hindered by increasing flow temperatures, and the effect was related to the influence of gas viscosity on ΔP, in accordance with Darcy's law. Casting quality with molten titanium (CP Ti) was directly proportional to the permeability level of the spinel-based investments. However, the high reactivity of the silica-based investment RP and the formation of α-case during casting hindered the benefits of the highest permeability level of this commercial brand.
Keywords: Titânio; Fundição odontológica; Prótese dentária; Reabilitação oral